2019
DOI: 10.1590/1981-863720190005920180028
|View full text |Cite
|
Sign up to set email alerts
|

The use of audiovisual distraction eyeglasses as a resource in Pediatric dental care: a case series

Abstract: Objective: This study aimed to report a case series on the use of audiovisual distraction eyeglasses in children during dental care. Methods: The influence of the distraction tool on the children’s heart rate frequency and dental care experience was further investigated. The study children had their heart rate recorded during three clinical appointments and underwent the following procedures: 1) anamnesis; 2) modified atraumatic restorative treatment with the child wearing audiovisual eyeglasses; and 3) modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Therefore, a non-invasive approach such as distraction may be beneficial. Besides, several studies have shown that the use of audio visual (AV) aids in medical practice when used for short invasive procedures to reduce pain and anxiety of patients [12][13][14]. Nevertheless, there still lies a controversy regarding the effectiveness of AV aids during dental treatment procedures.…”
Section: Fig 2 Participant's Perception On the Use Of Virtual Reality (Vr) During The La Proceduresmentioning
confidence: 99%
“…Therefore, a non-invasive approach such as distraction may be beneficial. Besides, several studies have shown that the use of audio visual (AV) aids in medical practice when used for short invasive procedures to reduce pain and anxiety of patients [12][13][14]. Nevertheless, there still lies a controversy regarding the effectiveness of AV aids during dental treatment procedures.…”
Section: Fig 2 Participant's Perception On the Use Of Virtual Reality (Vr) During The La Proceduresmentioning
confidence: 99%
“…However, distraction-based non-aversive behavior management techniques seem to have better acceptance by parents. Distraction alters a child’s distress by disrupting attention and helping in the completion of the dental procedure with minimal stress [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%